The politics of fear vs. the politics of hope: analysing the 2015 Greek election and referendum campaigns. Issue 1 (1st January 2017) - Boukala, Salomi; Dimitrakopoulou, Dimitra
ABSTRACT: This paper deals with the discursive construction of in-groups and out-groups through a politics of fear and a politics of hope. It draws on the 2015 Greek election and referendum campaigns of the two main political parties – the radical left Syriza and the conservative New Democracy – and emphasises how they legitimised their political decisions via these two forms of politics. The Greek bailout referendum took place on 5 July 2015 in a climate of polarisation and insecurity. We assume that the referendum, at the campaign level, could be considered an extension of the January 2015 election campaign that was shaped on the basis of a synthesis of a politics of fear and a politics of hope. Using the discursive strategies of the Discourse Historical Approach (DHA), and especially argumentation strategies and the concepts of topos and recontextualisation, we illustrate the link between political communication, election campaign strategies and political discourse through the prisms of fear and hope. Drawing on the Spinoza 'affects', we intend to conduct an interdisciplinary study of the contemporary Greek political scene and to illustrate whether and how political rhetoric and communication strategies are conducive to political dichotomies.